Global burden landscape (1990–2021) of gallbladder and biliary tract cancer attributable to high body mass index in older adults and a projection to 2050 - Chen, Pingping; Qin, Wenhao; Hu, Bing (Journal of Gastrointestinal Oncology, 2026)
Background: Obesity and population aging significantly influence the disease burden of gallbladder and biliary tract cancers (GBTCs). The burden of GBTC attributable to a high body mass index (BMI) among older adults was determined using data from the Global Burden of Disease (GBD) Study 2021.Methods: GBTC trends in deaths, disability-adjusted life years (DALYs), and age-standardized ratios (ASRs) were examined for different populations, geographic regions, and socio-demographic index (SDI) levels. Stratified clustering by estimated annual percentage change (EAPC) was used to assess patterns of change in the burden of disease in different geographic regions. Predictive modeling was performed using autoregressive integrated moving average modelling to estimate future disease burden.Results: A total of 360,029 DALYs and 17,976 deaths were attributed to high BMI-related GBTC among older adults globally in 2021. Sex analysis showed that older women had a higher burden of disease, whereas the burden of disease had increased among older men over the last three decades. Moreover, the burden of disease had been heaviest in areas with high SDI, while it had increased significantly in countries with low and medium SDI. Regional analyses of GBD data showed that Asia had the highest burden of disease.Conclusions: The global burden of GBTC due to high BMI in older adults over the past three decades was comprehensively analyzed. Targeted public health strategies should be implemented to reduce this burden.